Analysis of The Relationship Between Sleep Quality and The Incidence of Hypertension at Productive Age in The Working Area of The Tamalanrea Health Center - Maryam Jamaluddin; Nurafriani; Nurbaya Sitti (Althar Cendikia Education, 2026)
Hypertension is a major global public health problem and a leading risk factor for cardiovascular disease. Although commonly associated with older adults, its prevalence has increased among individuals of productive age due to unhealthy lifestyles, including poor diet, physical inactivity, smoking, alcohol consumption, stress, and inadequate sleep. Poor sleep quality has emerged as a modifiable risk factor for hypertension. This study aimed to examine the relationship between sleep quality and hypertension among adults of productive age using a quantitative cross-sectional design. Data were analyzed to assess the association between sleep quality and hypertension status. The results showed a significant relationship between sleep quality and hypertension (p = 0.001), indicating that individuals with poor sleep quality were more likely to experience hypertension. These findings are consistent with previous studies reporting an increasing prevalence of hypertension among younger and productive-age populations, partly attributable to insufficient sleep and late-night gadget use. High work demands and busy daily routines may contribute to impaired sleep quality, thereby increasing the risk of hypertension. In conclusion, poor sleep quality is significantly associated with hypertension among productive-age adults, highlighting the importance of promoting healthy sleep habits as part of hypertension prevention strategies.